A GEOSPATIAL APPROACH ON EXAMINING THE INTERACTION BETWEEN SHIFTING WEATHER AND MENTAL HEALTH OF CONSTRUCTION WORKERS AT SPECIFIC SITES OF CHENNAI CITY - R, JAGANATHAN; A, SONA; R V, SHURMILI (Innovare Journal of Social Sciences, 2023)
Objectives: Urbanization is one of the most important global developments of the 21st century, and it has a substantial impact on health. Because of immigration, urbanization may generate challenges such as stressful events, a poor social network, and excessive city growth. Along with these circumstances, shifting weather conditions can have a negative impact on mental health, making it a critical procedure that must not be underestimated. Methods: This study uses geospatial technology to access the relationship between shifting weather and the mental health of construction workers in different construction sites of Chennai city zones. The data sets used for this cross-sectional study will be temperature data for two different months, that is, the hottest month (June) and the rainy month (July) along with the mental health data. This data set used here helps to evaluate the difference in workers’ mental health in higher temperature month and low-temperature month. Results: The main finding shows that even minor fluctuations in the average temperature have resulted in a significant rise in mental distress and cases of severe heat-related illness. Based on the variation in temperature, the works have mentally changed the way of overviewing the works. The outcome explains that exposure to sun throughout working hours has increased mental distress. Conclusion: With regard to the result, we can conclude that higher temperatures are associated with an increase in mental illness including self-reported instances of poor mental health. Cold temperatures diminish negative mental health effects, whereas hot temperatures aggravate them. The findings imply that temperature has a considerably different effect on mental health than it does on physical health and that it has a relatively similar effect on other behavioral and psychological consequences.